Introduction - Henry, Rosita (The Australian journal of anthropology, 2000)
This introduction contextualises the papers in the Special Issue by briefly reviewing anthropological interest in dance to date, and by providing a challenge to received wisdom regarding the significance of expressive cultural forms. We theorise dance practices as domains of lived experience, and position movement as a performative moment of social interchange that is not merely reflective of prior political, personal, social and cosmological relations, but also constitutive of them. We argue that a renegotiation of the relationship between dance and anthropology is required so that dance is given full recognition as an active, fraught and dynamic force in human social life.